Teachers’ Strategies in Teaching Vocabulary to Young Learners Through Short Stories as Literary Media in ELT at SDN 163 Pekanbaru - Cut Raudhatul Miski; Indah Yohana; Irma Aulia; Nurliana Nurliana; Sari Khomariah (Institut Teknologi Pendidikan Indonesia, 2026)
This study investigates the strategies employed by an English teacher in teaching vocabulary to young learners through short stories as a literary medium at SDN 163 Pekanbaru. A descriptive qualitative design was applied, involving one Class V English teacher as the participant. Data were collected through classroom observation conducted on April 28, May 5, and May 8, 2026, a semi-structured teacher interview, and an observation checklist comprising 27 indicators across four lesson stages. The findings reveal that the teacher consistently applied multi-stage vocabulary teaching strategies encompassing schema activation during lesson opening, multi-modal vocabulary introduction through visual and gestural scaffolding, interactive and communicative practice activities, and structured lesson closure with formative assessment. A total of 26 out of 27 indicators were observed across three sessions. The only unobserved indicator was dramatic role-playing. This study concludes that short stories serve as an effective literary medium for vocabulary teaching when supported by systematic, learner-centered strategies that align with the cognitive and affective needs of young learners.